2020
DOI: 10.1039/d0qi00208a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and stable CsPbBr3 perovskite quantum dots by encapsulation in dual-shell hollow silica spheres for WLEDs

Abstract: A highly stable and efficient CsPbBr3@SiO2 composite phosphor is achieved by protecting the CsPbBr3 QDs from direct exposure to the atmosphere by encapsulating CsPbBr3 into dual-shell hollow silica nanospheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Recently, all‐inorganic CsPbX 3 (X = Cl, Br, I) nanocrystals (NCs) have attracted broad attention as promising candidates in light‐emitting diodes (LEDs), [ 3–8 ] solar cells, [ 9–11 ] lasers, [ 12–14 ] and photodetectors, [ 15–17 ] owing to their excellent optoelectronic properties, including high photoluminescence quantum yield (PLQY), wide tunable emission and narrow emission spectrum. [ 18–20 ] The relatively higher stability renders CsPbBr 3 NCs wide research, but the reported ones still suffer from poor heat and moisture stability, limiting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, all‐inorganic CsPbX 3 (X = Cl, Br, I) nanocrystals (NCs) have attracted broad attention as promising candidates in light‐emitting diodes (LEDs), [ 3–8 ] solar cells, [ 9–11 ] lasers, [ 12–14 ] and photodetectors, [ 15–17 ] owing to their excellent optoelectronic properties, including high photoluminescence quantum yield (PLQY), wide tunable emission and narrow emission spectrum. [ 18–20 ] The relatively higher stability renders CsPbBr 3 NCs wide research, but the reported ones still suffer from poor heat and moisture stability, limiting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The use of various synthesis strategies has led to a variety of possible structures of the resulting composite nanostructured materials. pNCs can be placed on the outer shell of silica (SiO 2 ) spheres via bonding to ligands [ 7 ]; a hollow matrix can be filled with pNCs [ 8 ]; silica layer can be grown on the pNC leading to the formation of core-shell structure [ 9 ]. Another way to fabricate composites is embedding of pNCs into a porous inert matrix is the straightforward and widely used method to achieve perovskite-based composites with stable performance [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silica (SiO 2 ) is a versatile material usually treated as a prospective candidate to resolve the long-standing bottleneck stability issue in nanostructure materials 11 , 15 , 16 . We note that the silica encapsulation has been well documented over the last decade using in-situ and ex-situ synthetic routes to enhancing the stability of the PQDs 17 21 .…”
Section: Introductionmentioning
confidence: 99%